Reviewing the civil military relations in Nepal - Barakoti, Manoj (Unity Journal, 2020)
An exegesis of the civil military relationship of Nepal in its entirety was maintained to examine its historical trend and to generate lessons for future direction. Review of historical materials, opinions of national and international scholars through different time spans, and study of the evolution of civil military relationship from medieval to modern Nepal was carried out. A critically meticulous analysis showed that the civil military relationship in Nepal has been cordial throughout history and the nature of the army has gradually changed from feudal clan based aggregation to a professional army. Much of this professionalism in the army began during the unification campaigns. Deliberation on the issue of the civilian control of the NA showed that it will be utterly unwise to produce civilian shoulders and that we need to stick to a professional army unless a grave danger to our sovereignty materializes. The activities of the army should always be controlled by a duly elected government and its expenses and actions checked and ratified by the parliament. It was concluded that the media image of the NA should remain open, accessible, and politically neutral, and that the army should continue its construction and humanitarian works, both within and beyond the borders. All concerned stakeholders must strive to maintain a harmonious civil military relationship in Nepal.